Evidence of Synaptic and Neurochemical Remodeling in the Retina of Aging Degus - Chang, Lily Y.-L.; Ardiles, Alvaro O.; Tapia-Rojas, Cheril; Araya, Joaquin; Inestrosa, Nibaldo C.; Palacios, Adrian G.; Acosta, Monica L. (Frontiers in Neuroscience, 2020)
Accumulation of amyloid-beta (Aβ) peptides is regarded as the hallmark of neurodegenerative alterations in the brain of Alzheimer’s disease (AD) patients. In the eye, accumulation of Aβ peptides has also been suggested to be a trigger of retinal neurodegenerative mechanisms. Some pathological aspects associated with Aβ levels in the brain are synaptic dysfunction, neurochemical remodeling and glial activation, but these changes have not been established in the retina of animals with Aβ accumulation. We have employed the Octodon degus in which brain and retina express increased levels of Aβ peptides accumulated in the brain and retina as a function of age. This current study investigated microglial morphology, to quantify expression of PSD95, synaptophysin, Iba-1 and choline acetyltransferase (ChAT) in the retina of juvenile, young and adult degus using immunolabeling methods. Neurotransmitters glutamate and gamma-aminobutyric acid (GABA) were detected using immunogold labeling and glutamate receptor subunits were quantified using Western blotting. There was an age-related increase in presynaptic and a decrease in postsynaptic retinal proteins in the retinal plexiform layers. Immunolabeling showed high changes in microglial activation morphology characteristic of intermediate stages of activation around the optic nerve head (ONH) and decreased microglial decreasing activation towards the peripheral y of the retina. Neurotransmitter expression pattern changed at juvenile ages but was similar in adults. Collectively, the results suggest that progressive activation of microglial activation, towards the periphery of the retina synaptic remodeling and neurotransmitter changes may be consequent to, occur due to or parallel to Aβ peptide and phosphorylated tau accumulation in the retina.